Making Space through Urban Materiality: Insights from Evolving Neighborhoods of Butwal, Nepal - Bhandari, Amrit Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Material possession and consumption have become prominent features of recent urbanism in Nepal. Urban dwellers tend to associate urban identity with the possession of certain materials, as evidenced in their choices for daily household use, housing design, clothing style, and other lifestyle elements. This paper examines how urban materiality has become ingrained in the daily social and cultural lives of the dwellers of these areas and how they use it to create their distinct space in the neighborhood. It also explores how new dwellers form mental associations with materials associated with urbanity in their homes and neighborhoods, striving to integrate them into their daily lives. It also analyzes how urban dwellers use such materials as signifiers of distinction and identity within the neighborhoods. Based on an analysis of first-hand qualitative data generated through ethnographic fieldwork in popular migrant destinations in Butwal city, such as Devinagar, Shankarnagar, Drivertole, and Manigram, this paper shows that urban residents in these areas prioritize urban material culture in their homes and neighborhoods, integrating it into daily life to shape social status and identity. It further demonstrates how objectively neutral material items become subjective, value-laden entities that contribute to social segregation in the neighborhood. Ultimately, it concludes that urban materiality reinforces family status within neighborhoods, thereby distinguishing and segregating families from one another.